Colonization and performance of a pyrene-degrading bacterium Mycolicibacterium sp. Pyr9 on root surfaces of white clover. (January 2021) - Yang, Jie; Gu, Yujun; Chen, Zhigao; Song, Yao; Sun, Fengfei; Liu, Juan; Waigi, Michael Gatheru
Abstracts: Some rhizosphere bacteria could colonize on the root surface of plants, or even form biofilm to promote plant growth, enhance plant resistance to harsh external environments and block the soil contamination. In this study, to explore the effects of pyrene-degrading bacterium on root surface on plant uptake of pyrene, a pyrene-degrading bacterium Mycolicibacterium sp. Pyr9 was isolated from the root surface of Eleusine indica L. Gaertn. in PAH-contaminated fields; after antibiotic labeling, it was colonized onto the root surface of white clover ( Trifolium repens L.), and its distribution and performance were monitored under different levels of pyrene contamination. Strain Pyr9 could degrade 98% of pyrene (with an initial concentration of 50 mg L −1 ) in culture solution within 8 d; it also owns a variety of plant growth promoting characteristics and appreciable tolerance to harsh environments. The transcription of pyrene catabolic genes in Pyr9 enhanced obviously when induced by pyrene. Pyr9 colonized and grew well on the root surface of white clover via root inoculation; some cells could even enter into the root tissues and move to the shoots. Compared with the Pyr9-free treatment, the pyrene contents in the roots and shoots of Pyr9-inoculated white clover decreased by 25%–30% and 33%–42%, respectively. Correspondingly, the pyrene accumulation and translocation factors in white clover decreased as well. These results indicate that Pyr9 would be a good potential to circumvent plant pyrene pollution. This research may provide a theoretical basis and technical support for the safety of agricultural products and human health in PAH-contaminated sites. Highlights: Pyrene-degrader Pyr9 owns a variety of plant growth promoting characteristics. Transcription of pyrene catabolic genes in Pyr9 enhanced when induced by pyrene. Strain Pyr9 colonized and grew well on the root surfaces of white clover. Pyrene content in white clover decreased significantly after Pyr9 inoculation.